PENERAPAN PENDEKATAN PAIKEM UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 29 PEKANBARU - Rahmi, Emelda; Marhadi, Hendri; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted because of the low learning result of IPS of third grade students of SDN 29 Pekanbaru, KKM determined at school, that is 75. From 36 students, reaching KKM is only 10 students (27,78%), while students who have not reached The KKM is 26 students (72.22%) with an average grade grade of 64,17. To overcome these problems then the researchers apply approach PAIKEM. The purpose of this study was to improve the learning outcomes of IPS students class III SDN 29 Pekanbaru with the application of approach PAIKEM. The result of the research got the average score of base score 63,75 increase in cycle I equal to 9,94% become 70,55. In cycle II the average score of students also increased by 25.10% to 80.28. In the basic score of classical completeness learning IPS student is 27.78% (not complete). After applied PAIKEM approach I cycle of student's classical learning completeness increased by 47,22% (not complete) and in cycle II of student's classical learning completeness increased by 83,33% (complete). Teacher activity at the first meeting of the first cycle of the percentage was 58.33% with sufficient category. The second meeting increased to 70.83% with good category. At the first meeting of the second cycle of teacher activity increased to 83.33% with very good category. At the second meeting it increased to 91.67% with very good category. Student activity at first meeting of cycle I the percentage is 54,16% with enough category. The second meeting increased to 70.83% with good category. At the first meeting of the second cycle of student activity increased to 79.16% with good category. At the second meeting it increased to 91.67% with very good category. From this research can be concluded that by applying PAIKEM approach can improve the learning result of IPS student of class III SDN 29 Pekanbaru.Keywords: Paikem approach, learning outcomes